Analisis Kebutuhan SDM Petugas Rekam Medis di Rumah Sakit Mekar Sari Bekasi Menggunakan Metode ABK-Kes - Fani Nur Azizah; Puteri Fannya; Laela Indawati; Bangga Agung Satrya (Yayasan Literasi Sains Indonesia, 2025)
Human resource planning is essential to ensure the availability of a workforce that meets current and future service needs. In the health sector, the health workload analysis method is used to objectively evaluate human resource needs. This study was conducted at Mekar Sari Bekasi Hospital to determine the ideal number of medical record and health information officers. Currently there are 9 medical record officers, consisting of 4 people with PMIK (Medical Recorder and Health Information) education backgrounds and 5 non-PMIK people. Conditions in the field show that officers often get additional workloads when colleagues are absent, and even have to work overtime to get the job done on time. This study uses descriptive quantitative methods through direct observation and interviews. The results show that the available work time (WKT) is 1201 hours or 72,000 minutes per year. With a Supporting Task Factor (FTP) of 8% and a Supporting Task Standard (STP) of 1.09, the ideal HR requirement is 10 people. This requires the addition of 1 officer with a PMIK background, who will be placed in the assembling section. Meanwhile, 1 officer each from the coding and filing sections will be transferred to the filing section.